Who Needs Diabetes Education? A Qualitative Analysis of Emerging Adults With Type 1 Diabetes. Issue 6 (December 2021) - Porter, Margot E.; Litchman, Michelle L.; Grigorian, Ernest G.; Blanchette, Julia E.; Allen, Nancy A.
Background: The purpose of this study is to explore the diabetes self-management education (DSME) needs of emerging adults with type 1 diabetes mellitus (T1DM) because addressing these needs may facilitate optimal glycemic management during this challenging transitional period. Methods: A hybrid qualitative design was utilized. Emerging adults and parents of emerging adults were recruited from endocrinology and primary care clinics and through a Utah-specific T1DM online community. Interviews were conducted to asses needs to achieve target A1C. Data were interpreted thematically. Results: Emerging adults with T1DM (N = 33) and parents of emerging adults with T1DM (N = 17) were interviewed. Three main themes emerged: (1) mixed desire for personal DSME; (2) I don't need the education, others do; and (3) health care provider (HCP) attributes that make a difference. Associated subthemes were reported. Conclusions: Emerging adults reported that further education for themselves was not needed, although newly diagnosed individuals would benefit from increased training in diabetes management. Although many emerging adults had a supportive social network, they endorsed the need for greater public education to avoid diabetes misinformation. Emerging adults felt more connected with HCPs that had diabetes-specific training (ie, endocrinologist) or those who personally live with T1DM.